Experimental and Theoretical Study of the Reaction Kinetics of 2,5-Dimethylterephthalonitrile Bromination Compared to 1,4-Dimethylbenzene Bromination - Villalba, Cibeli M. A.; de C Rozada, Thiago; dos Santos, Fábio S.; Scorsin, Leandro; Garcia, Jarem R.; Fiorin, Barbara C. (Synthesis, 2018)
Experimental and theoretical studies showed the differences observed in the benzylic tetrabromination reactions in 2,5-dimethylterephthalonitrile compared to 1,4-dimethylbenzene. It was observed that the compound containing the nitrile substituent underwent a slower bromination reaction, with the formation of four intermediate compounds, while for the compound without substituents, the reaction was faster and only two intermediate compounds were observed.
Keywords: bromination reactions; 1,4-dimethylbenzene; 2,5-dimethylterephthalonitrile; α,α,α′,α′-tetrabromide-p-xylene; α,α,α′,α′-tetrabromide-2,5-dicyano-p-xylene